IMPACT OF SERVICE QUALITY AND SERVICESCAPE ON CUSTOMER RETENTION MEDIATED BY CUSTOMER SATISFACTION AT SSAMAYA BALINESE SPA - Fiktor Tandi Pasapan; J.E. Sutanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
Spa industry is part of experience-based services, faces increasing challenges in retaining customers amid intensifying competition. This study aims to examine the effects of service quality and services cape on customer retention, with customer satisfaction as a mediating variable at Ssamaya Balinese Spa. This research employed quantitative approach using a survey of 220 repeat customers. Data were analyzed using SmartPLS4 and the findings reveal that service quality has a positive and significant effect on customer satisfaction and customer retention. Servicescape also exerts a positive and significant influence on customer satisfaction and customer. Furthermore, customer satisfaction positively and significantly affects customer retention and serves as a significant mediator in the relationships between service quality and customer retention. The concludes that service quality is the most influential factor in enhancing customer satisfaction and retention. Servicescape functions as a supporting factor that strengthens the overall customer experience through increased satisfaction.